PEMBERIAN E-SERTIFIKAT UNTUK MENINGKATKAN SEMANGAT BELAJAR SISWA DI SDN SIMOKERTO I/134 MASA PANDEMI COVID-19 - Dwi Lestari (Inteligensi : Jurnal Ilmu Pendidikan, 2021)
The purpose of this study was to determine the increase in students' enthusiasm for learning in terms of collecting assignments through the provision of e-certificates in Simokerto I/134 Elementary School in Surabaya during Covid-19 pandemic. The provision of this e-certificate is to increase student responsibility in working on collecting assignments on time. Considering that during online learning there are many obstacles experienced by students including device and internet network problems. In addition, students are more interested in online games than doing assignments given by the teacher. The results of this study explained that the enthusiasm of the second grade students of SDN Simokerto I/134 Surabaya in doing assignments and collecting them increased through the provision of e-certificates. Students compete to give their best and on time to get the e-certificate. This provision can be considered as a reward so that students will increase their enthusiasm for learning, along with that student learning outcomes also increase. For this reason, in learning, the teacher should provide a new innovation so that students are more interested and enthusiastic in participating in learning in class.